Access to 3‐(2‐Oxoalkyl)‐azaspiro[4.5]trienones via Acid‐Triggered Oxidative Cascade Reaction through Alkenyl Peroxide Radical Intermediate. Issue 3 (7th December 2018) - Wang, Chang‐Sheng; Roisnel, Thierry; Dixneuf, Pierre H.; Soulé, Jean‐François
Abstract: Azaspiro[4.5]trienones bearing ketone side chains at the 3‐position are prepared from N ‐alkyl‐arylpropiolamides and ketones via oxidative 1, 2‐difunctionalization of alkynes. The cascade sequence starts with the generation of alkenyl peroxide intermediates, which are obtained by addition of tert ‐butyl hydroperoxide to ketones in presence of a catalytic amount of a strong acid. Then, the ketone radical adds to alkynes, followed by spirocyclization and dearomatization process. This method represents a new example of difunctionalization of alkynes with simultaneous formation of two carbon−carbon single bonds and one carbon−oxygen double bond in one step. Abstract :